Developing a competency framework for broad-based black economic empowerment verification practitioners - Seate, Barbara Makhosazana (Vaal University of Technology, 2014)
The influence of measuring Broad Based Black Economic Empowerment (B-BBEE) is becoming a vital issue in organisations simply because it affects the organisation in different ways. Organisations seek ways to improve their B-BBEE status level in order to be conducive when conducting business and they believe that B-BBEE is necessary. The B-BBEE verification agencies are responsible for carrying out a factual, thorough evaluation of a measured entity’s B-BBEE status and, based on the result, for determining a B-BBEE score. The overall aim of conducting verification is to give confidence to all parties that rely upon the score set out in the verification certificate that the information on which the certificate is based has been tested for validity and accuracy. The study provided more information on how verification agencies can improve their competencies and how this affects the Department of Trade and Industry and the verification agencies. The study focused on educating the verification agencies and the Department of Trade and Industry about the importance and processes of developing a competency framework. Its purpose was to develop a competency framework for verification agencies. A survey consisted of about 300 verification practitioners employed by 80 verification agencies. Data was collected using the consensus sampling technique. All of these practitioners constituted a ‘universe’ or ‘population’ and 87 respondents were utilised. The Social Package for the Social Sciences (SPSS) and AMOS software packages were used for descriptive and factor analysis. Finally, the findings for the study are highlighted and the conclusions, implications and recommendations drawn.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Broad Based Black Economic Empowerment (B-BBEE); Competency Framework; Improve verification agencies competencies; Department of Trade and Industry; Economic empowerment; Dissertations, Academic -- South Africa; Black Economic Empowerment (Program : South Africa)